Effects of Providing Supplementary Foods of Duck Eggs and UHT Milk on the Physical Growth and Body Weight of Stunted Children - Marina, Marina; Harini, Rini; Horiwati, Dian; Andini, Sri Dewi; Rohmawati, Ayu; Nurindah, Resa (Indonesian Journal of Global Health Research, 2025)
Stunting is a global health problem that affects children's physical growth and cognitive development. In some areas of Serang Regency, the prevalence of stunting remains high, requiring effective nutritional interventions. Objective: To analyze the effect of supplementary feeding in the form of duck eggs and UHT milk on the growth and weight of stunted children. Method: This study used a quasi-experimental design with a one-group pre-post test approach. Conducted in Padarincang District, Serang Regency, in 2024. A sample of 125 stunted children was determined using total sampling technique. Data was collected using observation sheets and analyzed with paired t-test. Results: A significant increase was found in the weight and height of stunted children after the intervention, where body weight increased significantly (p-value = 0.017) and t-value = -2.425, while height also increased significantly (p-value = 0.006) and t-value = -2.774. Conclusion: The consumption of two duck eggs and UHT milk has been proven to be effective in increasing the weight and height of stunted children. Therefore, parents are encouraged to provide sufficient sources of animal protein to support optimal child growth.